RESPONSES OF CYPRINUS CARPIO VAR . COMMUNIS TO CYHALO IN, A P E OID INSECTICIDE - Begum, A. Asia; Ramesh, M.; Noortheen, A.; Sampth, Hannah; Revathy, B. (Journal of Indian Fisheries Association, 2016)
Haematological and biochemical profiles in a freshwater teleost,Cyprinus carpio var. communis, exposed to sub-lethal toxicity of the insecticidecyhalothrin were studied. During the treatment, erythrocyte count,haemoglobin content and protein content decreased, whereas leucocyte countand glucose level increased. The data are discussed in relation to thesignificance of haematological and biochemical changes as non-specificbiomarkers against anthropogenic stress.Keywords: Cyhalothrin, erythrocytes, leucocytes, haemoglobin, protein,glucose, Cyprinus carpio